Analisis Skala Usaha Dan Finansial Minyak Sere Wangi (Cymbopogon nardus rendle. Lin) Di Kabupaten Gayo Lues - Fauzah Aziz; Indra zainun; Abubakar Karim (JURNAL AGRICA, 2021)
Sere Wangi is a plantation commodity which is the prima donna in Gayo Lues Regency with the largest production compared to the production of other commodities. The contribution of the plantation sub-sector to the regional economy is also quite large because in Gayo Lues Regency, up to now, there have been many activities in the plantation business, especially the Sere Wangi plant. The purpose of this study was to determine the scale of business and financial business of citronella farming which is processed into citronella oil in Gayo Lues Regency. The research was conducted in Gayo Lues Regency, with a descriptive method. The research method is survey with sampling done by purposive sampling with the amount of data taken by farmers as many as 99 respondents and traders as many as 10 respondents. The research results of sere wangi farmers have obtained profits with an average production of citronella oil of 164.55 kg / year, with a minimum cultivated area of 0.67 ha or 6,657.09 M2, farmers have BEP for land area. Financially, sere wangi farming is feasible to continue to be developed with a Net Benefit Cost Ratio (NBCR) value of 2.57. This means that every one rupiah that is spent during the farming life of lemongrass produces Rp 2.57 units of net benefits.Keywords: Citronella Oil, Business Scale, Feasibility. BEP